Effect of feeding technique and prey characteristics on the feeding rate of Olrog's Gulls (Larus atlanticus) - Suarez, Nicolas Marcelo (2013)
The Olrog's Gull (Larus atlanticus) is a species that feeds almost exclusively on intertidal crabs. The influence of feeding technique, food source, and habitat characteristics on the feeding rate of breeding individuals was examined at Bahía San Blas, Argentina, from September to December 2007. Olrog's Gulls used four feeding techniques, with more prey captured by pecking than by peck-digging, head submergence, or up-ending. Olrog's Gulls fed throughout the tidal cycle using different intertidal zones when they were exposed and covered by water. However, feeding techniques used in exposed intertidal areas (pecking and peck-digging) resulted in significantly higher feeding rates. Feeding rate increased with average prey density and was higher when feeding in structured environments, characterized by the presence of rocks or oysters and high densities of the intertidal crab Cyrtograpsus altimanus. The burrowing crab Neohelice granulata is the main component of the Olrog's Gull diet during most of the breeding cycle. Although average density of N. granulata in feeding patches was lower than that of C. altimanus, body size of the former was significantly larger and energy density of individuals higher, resulting in a higher energy profitability of unstructured habitats. Prey switching toward C. altimanus during the young chick stage observed in previous studies may result from the need to feed chicks with smaller prey.